Reviewing the potential of probiotics, prebiotics and synbiotics: advancements in treatment of ulcerative colitis - Jadhav, Apurva; Jagtap, Suresh; Vyavahare, Suresh; Sharbidre, Archana; Kunchiraman, Bipinraj (Frontiers in Cellular and Infection Microbiology, 2023)
Inflammatory bowel diseases (IBD) like Crohn’s and ulcerative colitis (UC) are multifactorial pathologies caused by environmental factors and genetic background. UC is a chronic inflammatory disorder that specifically targets the colon, resulting in inflammation. Various chemical interventions, including aminosalicylates, corticosteroids, immunomodulators, and biological therapies, have been extensively employed for the purpose of managing symptoms associated with UC. Nevertheless, it is important to note that these therapeutic interventions may give rise to undesirable consequences, including, but not limited to, the potential for weight gain, fluid retention, and heightened vulnerability to infections. Emerging therapeutic approaches for UC are costly due to their chronic nature. Alternatives like synbiotic therapy, combining prebiotics and probiotics, have gained attention for mitigating dysbiosis in UC patients. Prebiotics promote beneficial bacteria proliferation, while probiotics establish a balanced gut microbiota and regulate immune system functionality. The utilisation of synbiotics has been shown to improve the inflammatory response and promote the resolution of symptoms in individuals with UC through the stimulation of beneficial bacteria growth and the enhancement of intestinal barrier integrity. Hence, this review article aims to explore the potential benefits and underlying reasons for incorporating alternative approaches in the management of UC with studies performed using prebiotics, probiotics, and synbiotics to treat ulcerative colitis and to highlight safety and considerations in UC and future perspectives. This will facilitate the utilisation of novel treatment strategies for the safer and more efficacious management of patients with UC.